2016
DOI: 10.1159/000443618
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Perfusion Improves Diagnostic Accuracy in Acute Posterior Circulation Stroke

Abstract: Background and Purpose: Computed tomography perfusion (CTP) has a high diagnostic value in the detection of acute ischemic stroke in the anterior circulation. However, the diagnostic value in suspected posterior circulation (PC) stroke is uncertain, and whole brain volume perfusion is not yet in widespread use. We therefore studied the additional value of whole brain volume perfusion to non-contrast CT (NCCT) and CT angiography source images (CTA-SI) for infarct detection in patients with suspected acute ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 10 publications
1
31
1
Order By: Relevance
“…Concordant to other studies, our findings confirmed that CTP in PC allows to detect significantly more ischaemic strokes than NCCT [4,5,39]. As NCCT presented low SE and ACC values, the addiction of CTP in the diagnostic work-up in our patients suspected of an ischaemic posterior circulation stroke significantly increased diagnostic ACC.…”
Section: Ischaemic Lesion Detectionsupporting
confidence: 91%
See 1 more Smart Citation
“…Concordant to other studies, our findings confirmed that CTP in PC allows to detect significantly more ischaemic strokes than NCCT [4,5,39]. As NCCT presented low SE and ACC values, the addiction of CTP in the diagnostic work-up in our patients suspected of an ischaemic posterior circulation stroke significantly increased diagnostic ACC.…”
Section: Ischaemic Lesion Detectionsupporting
confidence: 91%
“…The diagnostic value of CTP in the posterior circulation has been little investigated with few evidences of its reliability and accuracy; moreover, the diagnostic effects of RAPID introduction in the evaluation of infratentorial ischaemic changes have not yet been clarified [3,4,[38][39][40]. To the best of our knowledge, these are the first reported instances of PC stroke patient selection using RAPID from European countries.…”
Section: Aim Of the Studymentioning
confidence: 97%
“…A subgroup analysis from the Dutch Acute Stroke Trial (DUST) showed that the addition of CTP increases the detection rate of early ischaemic changes in the posterior circulation compared to combinatory NCCT and CTA [7]. Another study found similar results, suggesting an increase of sensitivity for the detection of ischaemic lesions with the addition of CTP in CTbased imaging of acute vertebrobasilar stroke [6].…”
Section: Discussionmentioning
confidence: 93%
“…Few other studies have tested the performance of CTP in this stroke territory [6][7][8][9][10]14]. A subgroup analysis from the Dutch Acute Stroke Trial (DUST) showed that the addition of CTP increases the detection rate of early ischaemic changes in the posterior circulation compared to combinatory NCCT and CTA [7].…”
Section: Discussionmentioning
confidence: 99%
“…Ninth, only NCCT images were used for infarct prediction. Although computed tomographic perfusion imaging (CTP) may improve detection rates of posterior circulation ischemia [23], CTP images are difficult to interpret and can lead to false positive results [25]. Furthermore, the limitation to NCCT scans improves general applicability of the algorithm in clinical routine and retrospective studies, as not all hospitals perform CTP imaging in respective acute situations.…”
Section: Discussionmentioning
confidence: 99%